Desde el Sur journal guidelines for the authors of articles - Sur, Universidad Científica del (2019)
Desde el Sur, a journal edited by the General Courses Coordination of Universidad Científica del Sur (UCSUR), is a peer-reviewed semi-annual publication. It features previously unpublished research articles from all over the world in the fields of humanities and social sciences, preferably with a focus on Latin American issues. Desde el Sur is distributed free of charge in both its printed and online versions.